Utilization of Transportation Model for Profit Maximization for Strategic Cement Sdn Bhd - Lee, Chow Hooi (1997)
This project is entitled' Utilization of Transportation Model for profit maximization for Strategic Cement Sdn Bhd '. Transportation Model in this project is one class of linear programming which is one of the decision tool for solving problem in management science. The transportation model utilized in this project is based _on the modelling developed by Anderson et. af. . The objective of this project is to determine the optimum delivery schedule of cement from two plants of Strategic Cement Sdn Bhd to fulfill the demand of twenty three different locations/destinations in Peninsular Malaysia. The factors involved in determining the profit maximization of the company are cement selling price to the various destinations, production cost, paper bag cost, stevedoring cost, commission to distributors and transportation cost. The result generated by the Model shows that the optimum distribution pattern is following the profit or revenue maximum pattern i.e. delivery of cement to the maximum profit contribution areas. The trade-off in the Transportation Model is the unsatisfied or unfulfilled demand area or market share which will in tum affect customer satisfaction level. The current practice by Strategic Cement Sdn Bhd reveals that company is supplying to certain demand location/destination despite with lower profit margin as compared to the empirical result generated/guided by the Transportation Model. This is mainly attributed to the fact that in the real business world, other factors shall be taking into consideration besides profits , such as customer service, market share and long term business relationship.The sensitivity analysis reveals that 1% change of the variables and demand has direct effect on the profit margin and transportation schedule for the company. Management of Strategic Cement Sdn Bhd can therefore utilizes this information to control cost and delivery schedule to achieve higher profit margin.